Spatial ability and learning achievement in transformation geometry: A correlation study - Rustanuarsi, Ressy (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2025)
Spatial ability is one of the essential factors for individuals' success in learning geometry. However, limited studies have specifically explored the extent to which spatial ability affects students' achievement in transformation geometry. This study aims to investigate the correlation between spatial ability and the learning achievement of mathematics education students in transformation geometry courses. A quantitative approach with a causal-correlational design was employed. The population consisted of all fourth-semester students enrolled in the Mathematics Education Study Program at IAIN Pontianak, totaling 28 students. The entire population was selected as the sample using the total sampling technique. Data on spatial ability were collected through a spatial ability test, while data on learning achievement in transformation geometry were obtained through documentation. The collected data were analyzed using descriptive and inferential statistics, including correlation analysis, t-tests, and simple linear regression analysis. The findings reveal a positive and statistically significant relationship between spatial ability and learning achievement in transformation geometry. Consequently, lecturers must design strategies that effectively accommodate and enhance students' spatial abilities. Improving spatial ability is expected to contribute positively to students' learning achievement in transformation geometry courses.